Student Satisfaction with Online Learning in Vocational Education: An Extended Technology Acceptance Model Approach - Keswanto, Heru; Kurniati, Erisa; Sofwan , Muhammad (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aims to analyse student satisfaction with the quality of online learning services in vocational education, employing the TAM as the theoretical framework. It examines the relationships between perceived ease of use, perceived usefulness, and institutional support on student satisfaction, considering complexities such as digital literacy, platform quality, and the need for practical learning. Using a quantitative survey approach, data were collected from 53 purposively selected students via questionnaires and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that perceived ease of use (β = 0.634, p < 0.001) and institutional support (β = 0.450, p < 0.001) significantly influence student satisfaction, with perceived usefulness also contributing positively (β = 0.348, p < 0.001). However, limited teacher-student interaction highlights challenges in platform design and online pedagogical training. The study recommends enhancing interaction through digital platforms, diversifying learning resources, and improving technological infrastructure, such as internet connectivity, to support effective vocational education.